1990
DOI: 10.2307/1591254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lactose on Cecal pH, Bacteriostatic Volatile Fatty Acids, and Salmonella typhimurium Colonization of Broiler Chicks

Abstract: One-day-old broiler chicks were inoculated with volatile fatty acid producing cecal flora from adult chickens. The chicks were divided into four groups and provided 1) no lactose, 2) 2.5% lactose in water, 3) 5% lactose in feed, or 4) 10% lactose in feed, until 10 days of age. All groups were challenged at 3 days of age with 10(6) or 10(8) S. typhimurium. At 10 days, the number of Salmonella in the ceca of the chicks challenged with 10(6) Salmonella was significantly decreased (P less than 0.01) in the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 32 publications
3
53
1
2
Order By: Relevance
“…Salmonella contamination of chickens carcasses is very important from the health specialists' and consumers' perspective. It is demonstrated that the control of Salmonella is achieved by low pH and high level of volatile fatty acids in broiler caeca content (Corrier et al, 1990a(Corrier et al, , 1990b. In vitro studies showed that Salmonella typhimurium did not grow when FOS was the sole carbon source (Bailey et al, 1991), therefore feeding oligofructose may be a practical strategy for controlling Salmonella in chicks.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
“…Salmonella contamination of chickens carcasses is very important from the health specialists' and consumers' perspective. It is demonstrated that the control of Salmonella is achieved by low pH and high level of volatile fatty acids in broiler caeca content (Corrier et al, 1990a(Corrier et al, , 1990b. In vitro studies showed that Salmonella typhimurium did not grow when FOS was the sole carbon source (Bailey et al, 1991), therefore feeding oligofructose may be a practical strategy for controlling Salmonella in chicks.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
“…Organic acids, such as acetic, butyric, lactic, and propionic acids, can modify intestinal microbial growth and this prebiotic effect results in the production of short-chain fatty acids by bacteria. Short-chain fatty acids are thought to have an antibacterial effect by decreasing luminal pH (Corrier et al, 1990). Other organic acids, such as citric, fumaric, and malic acids, have been used as growth promoters in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The cecum is the site of highest colonization by Salmonella spp., as well as by other pathogenic species of the family Enterobacteriaceae, such as Escherichia coli, compared to other sites in the digestive tract (1) and its colonization is used as a parameter for the evaluation of the efficacy of treatment against salmonellosis (2, 3, 4, 8, 18, 19). This characteristic is related to the presence of specific receptors in the organ, to the physiology of cecal peristalsis causing a longer time of permanence of the food bolus and to pH, among other factors (8,9,18,32).…”
Section: Resultsmentioning
confidence: 99%
“…in the intestine of chickens (2,4,8,9,18,19,22,23,28,32). Its effect is due to the fact that lactose is not fully digested by chickens because of their lactase deficiency, with the carbohydrate reaching the cecum in practically intact form, and being fermented there by the cecal microflora which produces antagonistic substances against Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%